2018
DOI: 10.1155/2018/6120909
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Rural/Urban Homicide in Colombia, 1992-2015: Internal Armed Conflict and Hints for Postconflict

Abstract: Objective. To analyze the relationship between rural and urban homicide rates in Colombia between 1992 and 2015 and the fluctuations in these rates. Methods. Individual records of homicides and population aggregates in men and women aged 15-64 years were used. The adjusted rates of annual homicides were calculated for urban/rural areas and standardized by age. Rate Ratios (RRs) adjusted by region were calculated. A joinpoint analysis was performed to identify inflection points and the Annual Percentage Change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…This was confirmed in this study, where OR values showed statistically significant influence of symptoms of anxiety, depression and somatization on TMD and where all TMD diagnoses were found associated with each of the studied psychological factors. The psychological conditions have shown to be different between urban and rural zones, not only in Colombia [ 41 , 42 ], but also in other regions of the world [ 43 ]. The influence of psychological factors on TMD in Colombia, may have different conditions compared to other countries, from a demographic point of view.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed in this study, where OR values showed statistically significant influence of symptoms of anxiety, depression and somatization on TMD and where all TMD diagnoses were found associated with each of the studied psychological factors. The psychological conditions have shown to be different between urban and rural zones, not only in Colombia [ 41 , 42 ], but also in other regions of the world [ 43 ]. The influence of psychological factors on TMD in Colombia, may have different conditions compared to other countries, from a demographic point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados de este estudio muestran que, a diferencia de otros países, las variaciones en las tasas de homicidios en Colombia son más pronunciadas en las zonas rurales que en las urbanas (Vallejo et al, 2018). Para el caso de esta investigación, el 90 % de solicitudes para iniciar el protocolo de empleo de ECDRH se realizaron en sectores rurales.…”
Section: Revista Científicaunclassified
“…Globally, Serbia and Canada have explored the impact of aging and mental health services on disease mortality by gender subgroups, respectively [ 8 , 9 ]. The United States, Lithuania, Poland, and many other countries have extensively conducted epidemiological analyses of related disorders from an urban–rural perspective [ 10 , 11 , 12 , 13 ]. However, few epidemiological descriptions of injury and poisoning from an urban–rural perspective are available for mainland China.…”
Section: Introductionmentioning
confidence: 99%